PP137 Regional Process For Planning Medical Equipment Procurement In Italy. (2017) - Medici, Mario Fregonara; Bellelli, Stefania; Villarboito, Luciano; Pepe, Michela
Abstract : INTRODUCTION: An appropriate governance of the installed equipment base, by defining replacements strategies and programming introductions of innovative Biomedical Technologies (BT), has direct effects on the efficiency and effectiveness of health systems. An effective health technology management is of paramount importance for providing safe, high quality and innovative care with the constraint of health-care budgets, safeguarding equity, access and choice principles. Data from the regional BT information flow show that, compared to the gold standard (1), the North Region of Italy has about 15 percent less of large medical equipment younger than 5 years and about 15 percent more of equipment older than 10 years. METHODS: In order to draw a unified path of BT procurement processes, in 2013 and 2014 regional regulations (2, 3) were enacted. Each Public Hospital and Local Health Authorities (ASRs) defined a plan (PLTB) containing, regardless of the form of procurement and type of funding, all BT requests for a value greater than EUR40, 000 distinguished in replacement/new acquisition/upgrade, innovative acquisition and donations. Requests of BT have to obtain the authorization by the Regional Healthcare Authority Commission (GTB), in compliance with defined criteria, including financial and sustainability aspects, after the evaluation of the Regional Clinical Engineering Commission (GIC) supported by IRES, Health Technology Assessment and Management research group. RESULTS: Over the years 2014 and 2015, the ASRs submitted 491 BT requests, of which 87 percent were replacement/new acquisition/upgrade, 9 percent innovative acquisition and 4 percent donations. Altogether 26 percent of these instances were urgent and 2 percent were unique BT on the market. Sixteen percent of requests for replacement/new acquisition/upgrade of BT related to large medical equipment with mean age of 13.3 years, 2 percent regarded innovative BT with average age of 8.4 years and 48 percent widespread technologies with mean age of 15.6 years. CONCLUSIONS: The limitations in investments deriving from being a Region in "Recovery Plan", have originated an absence of BT programming, as shown in PLTB by the prevalence of requests for the replacement management of obsolete equipment with inadequate performance, high machine downtimes and elevated maintenance costs.